2019
DOI: 10.1097/bot.0000000000001504
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Knee Pain Beyond 1 Year: Suprapatellar Versus Infrapatellar Approach for Intramedullary Nailing of the Tibia

Abstract: Objective: To compare the magnitude of knee pain between the suprapatellar (SP) and infrapatellar (IP) approach for tibial nailing in patients who are more than 1 year after injury. Design: Retrospective cohort study. Setting: Academic Level I trauma center. Patients/Participants: All tibia fracture patients 18-80 years of age treated with an intramedullary tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Interestingly, a recent meta-analysis by Wang positioning whilst the knee was in a semi-flexed position [11]. Our meta-analysis does, however, include more, recently published high-quality studies [18,[20][21][22][23][24]. This data, when pooled, clearly show no difference in fluoroscopy time.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Interestingly, a recent meta-analysis by Wang positioning whilst the knee was in a semi-flexed position [11]. Our meta-analysis does, however, include more, recently published high-quality studies [18,[20][21][22][23][24]. This data, when pooled, clearly show no difference in fluoroscopy time.…”
Section: Discussionmentioning
confidence: 83%
“…Authors have hypothesised that post-operative knee pain is due to patellar tendon splitting, proximal nail protrusion, intra-articular structural damage and involvement of the infrapatellar nerve; the suprapatellar approach aims to avoid this [6,10]. However, it is difficult to conclude superiority of suprapatellar approach in terms of less post-operative pain as only 3 out of 12 studies used similar pain scoring systems [7,15,18]. Few other studies did mention about knee pain, but, unfortunately, they could not be included in our analysis due to insufficient reported data [17,21,23].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 , 26 , 27 However, other studies found no differences in anterior knee pain and functional outcomes if compared to IP-nailing. 10 , 12 , 28 Furthermore, data on theoretical concerns regarding retropatellar chondropathy and infection rates after the SP versus IP-approach are scarce. The most recent systematic review on this subject was published in 2019 in this Journal 20 and concluded that the SP-approach results in less pain and better functional outcomes if compared with IP-approach.…”
Section: Introductionmentioning
confidence: 99%